Cocaine increases serotonergic activity in the hippocampus and nucleus accumbens in vivo: 5-HT1a-receptor antagonism blocks behavioral but potentiates serotonergic activation. - Müller, C; Carey, R; De Souza Silva, MA; Jocham, G; Huston, J (2002)
The hippocampus is an important mediator of learning and reinforcement, but its role in cocaine effects has received little attention. Neuronal activity in the hippocampus and the nucleus accumbens (Nac) depend on serotonergic (5-HT) transmission. Here we describe for the first time a cocaine-induced increase in 5-HT concentration in the hippocampus and the Nac parallel to behavioral activation. In addition, pretreatment with the 5-HT(1A)-receptor antagonist WAY 100635 blocked the behavioral activation after cocaine while potentiating the 5-HT increase in the hippocampus and the Nac. In vivo microdialysis was used in behaving rats to measure extracellular concentration of 5-HT in the hippocampus and the Nac. Four groups of animals received one of the following drug combinations: WAY 100635 (0.4 mg/kg) and cocaine (10 mg/kg), saline and cocaine (10 mg/kg), WAY 100635 (0.4 mg/kg) and saline, or saline and saline. The injections were administered i.p. and spaced 30 min apart. It was found that 1.) cocaine, at a dose that activates behavior, increases 5-HT levels in the hippocampus and in the Nac, and 2.) 5-HT(1A)-receptor antagonism can cause a dissociation of the hippocampal and Nac 5-HT activity from behavioral activation after cocaine. These results are discussed within the framework of the hippocampal-accumbens projection and its contribution to behavioral activity. They suggest that the hippocampus may have a role in mediating the behavioral and neurochemical effects of cocaine.